Factors contributing to motivation to attend class at the selected IPTS in Kelantan / Tengku Noraini Tengku Anuar - Tengku Anuar, Tengku Noraini (2015)
The issues of class attendance are not new in education industry since. This study attempts to identify the influence of curiosity, challenge, lecturer's attributes and lecturer 's teaching methods towards class attendance . The sample of 234 ind inviduals studying in two IPTS i n Kelantan was selected. Questionnaires comprising six parts were sent directly to targeted segment. In the first part, the first few questions are related to personal information , second part until fifth part consists of twenty five questions which used to measure student's extrinsic and intrinsic motivation and last part is related to class attendance of the students. The study delineates that the four factors (curiosity, challenge, lecture's attribures and lecturer's teaching methods) significantly influence the class attendance which are curiosity (p=. 182, p<0.05), challenge (p=.201, p<0.05), lecturer's attributes ({3=.364, p<0.05) and teaching methods (p=.134, p<0.05) on student's class attendance. The most significant Independent variables (curiosity, challenge, lecture's attributes and lecturer's teaching methods) to dependent variable (class attendance) from beta value to be lecturer's attributes (p=.364, p<0.05). Results show (.423, .419, .549 and .438) for the four factors which below .7 that provides moderate positive towards class attendance among students at Cosmopoint College of Technology and UNITAR International University.